Analisis Perilaku Konsumen terhadap Minat Beli Produk Viral pada E-Commerce Shopee di Kota Makassar - Achmad Ridha; Sudirman Kati; Handayani Hasan; Lidya Anastasya (Indonesian Journal Publisher, 2024)
This study aims to analyze the influence of individual factors, psychological factors, and social environment factors on the purchase intention of viral products on E-Commerce Shopee among consumers in Makassar City. The research employs a quantitative approach with primary data collected through a questionnaire. The sample consists of 100 respondents selected using the Slovin formula sampling technique. Multiple regression analysis is applied to the data. The analysis results show that both individual factors and social environment factors have a positive and significant effect on the purchase intention of viral products, with t-values of 2.528 and 4.777 and significance levels of 0.013 and 0.000, respectively. In contrast, psychological factors have a positive but not significant effect on purchase intention, with a t-value of 1.910 and a significance level of 0.059. The conclusion of this study is that both individual and social environment factors significantly influence consumers' purchase intentions for viral products on Shopee, while the impact of psychological factors is statistically insignificant. These findings highlight the importance of personal and social aspects in influencing purchase decisions for viral products.